Potentials of community-based-ecotourism to improve human wellbeing in Cambodia: an application of millennium ecosystem assessment framework. Issue 5 (4th July 2021) - Kibria, Abu SMG; Behie, Alison; Costanza, Robert; Groves, Colin; Farrell, Tracy
ABSTRACT: Community-based Ecotourism (CBE) has been promoted and widely adopted as an approach for funding conservation initiatives, while at the same time contributing to the wellbeing of the host communities. However, it often fails to live up to its promise and thereby lets the local people return to their old ways of doing things. The study is to explore the potentials of CBE on the indigenous human wellbeing by conducting a case study in the Veun Sai-Siem Pang National Park (VSSPNP). For this research work, tourists, indigenous households, key informants, and local leaders were interviewed. We found that the participants received only 6% of the total revenue per year, despite 63% annual growth in number of tourists. The gibbons increased the recreational value of forest and significantly contributed to enhance tourist satisfaction. The program had significantly reduced their freedom for livelihood activities, and feeding condition of their families. On the contrary, it had significantly increased their groups and networks, and collective action and cooperation for conservation. But the wellbeing regarding basic materials and health conditions were not significantly changed by the ecotourism program. Therefore, without addressing the wellbeing of the participants, ecotourism programs would struggle in achieving sustainable outcomes.